BERTHA: Implementation of a four-component Dirac–Kohn–Sham relativistic framework - Belpassi, Leonardo; De Santis, Matteo; Quiney, Harry M.; Tarantelli, Francesco; Storchi, Loriano (The Journal of chemical physics, 2020)
In this paper, we present and review the most recent computational advances in the BERTHA code. BERTHA can be regarded as the state of the art in fully relativistic four-component Dirac–Kohn–Sham (DKS) software. Thanks to the implementation of various parallelization and memory open-ended distribution schemes in combination with efficient “density fitting” algorithms, it greatly reduces the computational burden of four-component DKS calculations. We also report the newly developed OpenMP version of the code, that, together with the berthmod Python module, provides a significant leap forward in terms of usability and applicability of the BERTHA software. Some applications of the recently developed natural orbitals for chemical valence/charge displacement bonding analysis and the real-time time dependent DKS implementation are also reported.